Pelatihan Pengelolaan Keuangan Rumah Tangga Bagi Ibu-Ibu Rumah Tangga Di Cengkareng Barat Wilayah Jakarta Barat - Swarmilah Hariani; Yulia Yustikasari; Taufik Akbar (LPMP Imperium, 2019)
This activity aims to increase understanding and knowledge of housewives in calculating and recording the receipt and expenditure of household cash properly so that expenses do not occur greater than income. So that the family's financial condition is always sufficient and has savings/investment for future needs so that welfare is realized for the family. The method used in this activity is in the form of training or short household financial management training using the financial management module. Participants are given training with activities using the classical method of giving material and followed by question and answer sessions and exercises/practices; the provision of working papers filled in accordance with the real conditions of the participant. Participants in the activity are housewives who do not work, housewives who work, and housewives who have their own business with an average educational background through high school, as well as the economic background of middle and lower families can attend training well and enthusiastically. Keyword: Household financial management, family welfare